2018
DOI: 10.1002/jbm.a.36320
|View full text |Cite
|
Sign up to set email alerts
|

In vivo immuno‐reactivity analysis of the porous three‐dimensional chitosan/SiO2 and chitosan/SiO2/hydroxyapatite hybrids

Abstract: Inorganic/organic hybrid silica-chitosan (CS) scaffolds have promising potential for bone defect repair, due to the controllable mechanical properties, degradation behavior, and scaffold morphology. However, the precise in vivo immuno-reactivity of silica-CS hybrids with various compositions is still poorly defined. In this study, we fabricated the three-dimensional (3D) interconnected porous chitosan-silica (CS/SiO ) and chitosan-silica-hydroxyapatite (CS/SiO /HA) hybrids, through sol-gel process and 3D plott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Next, we examined the levels of CD11b + monocytes 47-49 and F4/80 + macrophages 50 in the biomaterial microenvironment (CD11b is also expressed on some B-cells, neutrophils and macrophages 50 ). Consistent with prior observations 30,51 , implantation of aPLA+HA increased monocyte and macrophage proportions relative to sham controls, but incorporation of a.a. or 2DG did not reduce cellular recruitment (Fig. 3a-f).…”
Section: Resultssupporting
confidence: 90%
“…Next, we examined the levels of CD11b + monocytes 47-49 and F4/80 + macrophages 50 in the biomaterial microenvironment (CD11b is also expressed on some B-cells, neutrophils and macrophages 50 ). Consistent with prior observations 30,51 , implantation of aPLA+HA increased monocyte and macrophage proportions relative to sham controls, but incorporation of a.a. or 2DG did not reduce cellular recruitment (Fig. 3a-f).…”
Section: Resultssupporting
confidence: 90%
“…HAp is commonly used in TERM applications. Combination of HAp with various from of carriers such as electrospun fibers (Cai et al, 2017; Samadian et al, 2018), porous scaffolds (Guo M. et al, 2018), and hydrogels (Ghosh et al, 2017) have been reported for preparation of nanocomposite materials to modulate the desired cellular activities. Recently, graphene oxide-incorporated silicate-doped nano-HAp composites have been used for reinforcement of fibrous scaffolds of PCL produced by wet electrospinning for bone tissue engineering (Dalgic et al, 2018).…”
Section: Ceramic Nanoparticlesmentioning
confidence: 99%
“…The efficacy of HP was also widely proven in tissue engineering application for tendon and bone regeneration. The combination of HP with various carriers, such as porous [83] and electrospun [84,85] scaffolds or hydrogels [86] showed enhancement of cellular activity. In particular, the research underlined the HP capability of increasing the mechanical properties of the scaffolds and of supporting cell adhesion and differentiation into osteo-like cells, able to produce ECM.…”
Section: Orthopaedic Applicationsmentioning
confidence: 99%